To evaluate serum cortisol levels in patients with alcohol withdrawal delirium v/s patients with delirium due to any other disorder - Ishrat Sibia; Angad H. Singh; Rahul Joshi; Deepak Khanduja; Manish Bathla (Journal of Family Medicine and Primary Care)
Background: Delirium is an acute confusional state characterized by changes in the mental status, level of consciousness, impaired cognition, and inattention. It can develop within hours or days. Cortisol release from the hypothalamic–pituitary–adrenal axis (HPA) is vital for the host survival in stress. Biomarkers are used as an indicator of pathogenic processes or to assess the responses to a therapeutic intervention. To improve delirium recognition and care, investigators have identified possible biomarkers that may help in diagnosing individuals with delirium, assessing the severity of delirium. Cortisol has been suggested as biomarker for the diagnosis of delirium. Aims and Objectives: To evaluate and compare levels of serum cortisol in patients with alcohol withdrawal delirium with delirium due to other disorders. Materials and Methods: It was a cross-sectional prospective observational study. A total of 30 patients in Group A and 32 in Group B were included. The participants were evaluated based on delirium rating scale (DRS). Results: It was seen that in alcohol withdrawal delirium group, there was significant positive correlation between DRS score and serum cortisol level, i.e., with increase in DRS score, there was increase in serum cortisol levels and vice versa. Conclusion: Serum cortisol levels are associated and directly correlate with the occurrence and severity of delirium. Further studies are needed to elucidate the implications of this association for diagnosis and treatment.